Aircraft propulsion and gas turbine engines - El-Sayed, Ahmed F. (CRC Press, Taylor & Francis Group, 2017)
"AIRCRAFT PROPULSION and GAS TURBINE ENGINES, Second Edition, will be a significantly updated and expanded survey of today's aeronautical and aerospace propulsion. The book will be divided into three parts rather than two as in its 1st edition. The first two parts are devoted to air breathing engines, while the third part will handle non-air breathing or rocket engines. The first part investigates the performance of air/land gas turbines, while the second part deals with the description, analysis and design of gas turbine modules. This edition will exhibit major and minor changes compared with 1st edition. Major changes include the adding of three new topics; namely, piston engines together with integrated propeller coverage; pumps; and rocket propulsion. Rocket propulsion has been added, to serve courses that include aerospace topics as well as aircraft. A complete Solutions Manual and Exam Supplement will be available for qualified adopting instructors"--Provided by publisher